Ultra macroporous ZEO-1 molecular sieve, its synthesis method and its use
The germanium-free, high silica molecular sieve ZEO-1, with a three-dimensional cross-channel system, addresses the limitations of existing large-pore sieves by providing enhanced stability and catalytic activity, opening new industrial applications.
Patent Information
- Application Number
- JP2023532663
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-28
- Filing Date
- 2021-11-08
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2041-11-08
AI Technical Summary
The existing molecular sieves with large pores are limited by their stability, cost, and lack of multidimensional channels, which restricts their industrial applications, particularly in catalysis and adsorption processes.
The development of a germanium-free, high silica molecular sieve, ZEO-1, with a three-dimensional cross-channel system of (16+12)×(16+12)×(16+12)-membered rings, synthesized using a method that introduces titanium atoms into its framework, enhancing its stability and catalytic properties.
ZEO-1 exhibits improved structural stability and catalytic activity, offering new options for industrial catalysis and adsorption due to its large pore size and multidimensional channels, while avoiding the drawbacks of germanosilicates and other high-cost materials.
Smart Images

Figure 0007620101000009 
Figure 0007620101000010 
Figure 0007620101000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a silicate molecular sieve, ZEO-1, having extra-large pores, and further to a method for its synthesis, molecular sieve compositions comprising the molecular sieve, and uses thereof. [Background technology]
[0002] Molecular sieve materials are a category of inorganic microporous solid materials composed of TO4 (T represents an atom having an oxidation state of +4 or +3 under normal circumstances, such as Si, P, Al, B, Ge, Ga, etc., and the T atoms are tetrahedral atoms, i.e., framework atoms participating in the framework of the molecular sieve) tetrahedra through a common vertex. In general, the composition of a molecular sieve can be expressed by the following empirical chemical formula: x(M 1 / n AO2):yYO2:zR:qH2O, where M represents one or more organic or inorganic cations with valence +n, A represents one or more trivalent elements, Y represents one or more tetravalent elements, usually Si, and R represents one or more organic molecules. For molecular sieves with a specific structure obtained by a specific synthesis method, whether it is a freshly synthesized product or a sample after calcination treatment, its chemical composition usually has a certain range of variation. Furthermore, X-ray powder diffraction (XRD) is commonly used to distinguish molecular sieves with specific structures, since various crystallographic structures of molecular sieves have different channel structures and completely different diffraction patterns are obtained in X-ray powder diffraction patterns. The most important characteristics of molecular sieves are their variable channel chemical composition, adjustable channel size and channel shape. These excellent characteristics give molecular sieve materials a wide range of applications in the fields of adsorption, separation, catalysis, microelectronics, and medical diagnosis.
[0003] The uniqueness of molecular sieve materials with different structures is reflected in their unique X-ray powder diffraction patterns and different chemical compositions. The position, relative intensity and width of peaks in X-ray powder diffraction patterns are related to chemical composition, crystal size and crystal shape, etc., and the X-ray powder diffraction patterns of different samples may also be affected by the variation of unit cell parameters, which may cause slight differences in patterns. In addition, the uniqueness of molecular sieve materials with different structures may also be reflected in their unique topological properties. According to the definition and interpretation by the Structure Commission of the International Zeolite Association, for a particular molecular sieve topological framework, the coordination sequence and vertex symbols are unique when combined, i.e., they can be used to clearly distinguish different molecular sieve framework structures (see the official website of the International Molecular Sieve Association https: / / europe.iza-structure.org / IZA-SC / DatabaseHelp_Structures.html#CS). The commonly known molecular sieves such as Linde type A (zeolite A, see US 2,882,243), zeolite Y (see US 3,130,007), ZSM-11 molecular sieve (see US 3,709,979), ZSM-12 molecular sieve (see US 3,832,449), etc. all have unique X-ray diffraction patterns.
[0004] On the other hand, zeolites with the same structure generally have the same XRD pattern. However, two zeolite materials with similar XRD patterns and the same structure are considered to be different materials if the framework elements are different. Typical examples are molecular sieves TS-1 (see US4410501) and ZSM-5 (see US3702886), both of which have MFI topological structures. These are two different molecular sieve materials due to different framework elements, but have the same XRD pattern. Specifically, ZSM-5 molecular sieve contains Si and Al as framework elements, and therefore is mainly used in the field of acid catalysis, while TS-1 molecular sieve contains Si and Ti in the framework, and is mainly used as a catalyst in oxidation processes.
[0005] Furthermore, zeolites having the same topological structure, i.e., the same XRD pattern, and the same type of framework elements, but different relative contents of framework elements, may also belong to different molecular sieves. For example, zeolite X (see US2882244) and zeolite Y (see US3130007) are considered to be different molecular sieve materials, both of which have FAU topological structure, the same XRD pattern, and contain Si and Al as framework elements, but differ in the relative contents of Si and Al.
[0006] According to the number of rings in the channel, molecular sieving materials are divided into small-pore, medium-pore, large-pore, and extra-large-pore molecular sieves, which correspond to window rings with 8 or less rings, 10 or less rings, 12 or less rings, and more than 12 rings. The channel size of molecular sieving materials that have been successfully applied in industry is usually less than 1 nm, which greatly limits the molecular size and shape of the reactants in adsorption, separation, and catalytic reaction processes, and has been a constraint in the practical application of molecular sieving materials. It has always been a great challenge for inorganic chemists to develop and obtain stable extra-large-pore molecular sieves, even mesoporous molecular sieves, with channel diameters in the range of 1 nm to 2 nm. This class of materials should pave the way for novel catalytic applications in fields such as petrochemistry, fine chemicals, and life sciences.
[0007] Due to the stability of silicate materials, silicate extra-large pore molecular sieve materials have important application prospects. However, it is well known that large pores and extra-large pore silicate molecular sieves are very difficult to obtain, and the number of already synthesized silicate molecular sieve materials containing extra-large pore channel structures is very limited. To date, many compounds with more than 16-membered rings (including 16-membered rings) have been reported, such as the 30-membered ITQ-37 [J. Sun et al., Nature, 2009, 458, 1154-1157], the 28-membered ITQ-43 [J. Jiang et al., Science, 2011, 333, 1131-1134], and the 18-membered ITQ-33 [A. Corma et al., Nature 2006, 443, 842-845], NUD-1 [F.-J. Chen et al., Angew. Chem. Int. Ed. 2014, 53,9592-9596], and ECR-34 [KG Strohmaier et al., J. Am. Chem. Soc. 2003, 125, There are up to 20 kinds of extra-large pore silicate molecular sieve materials with the following characteristics: [16035-16039], but the majority of these mentioned materials are germanosilicate molecular sieves. In addition to being expensive, germanosilicate molecular sieves adsorb water and then undergo rapid framework collapse after removal of organic matter in the channels, which severely limits their large-scale industrial applications.
[0008] All the molecular sieves that have been widely industrialized or have industrial catalytic applications are molecular sieves with multidimensional channels, such as ZSM-5, zeolite Y, zeolite A, etc. Up to now, among all the new molecular sieves with known structures reported, all the stable pure silica or high silica extra-large pore molecular sieves do not have multidimensional extra-large pore channels. All the molecular sieves that contain multidimensional extra-large pores are always germanosilicate zeolite or aluminophosphate molecular sieve materials, whose stability and high cost limit their applications.
[0009] WO2013019462A1 discloses a synthetic extra-large pore silicate molecular sieve EMM-23 and a method for its synthesis. The method uses diquaternary ammonium cations in the synthesis to obtain a material with a pure silica framework, and the open channels of EMM-23 are adjustable 21-24 membered rings. However, the structure contains Si-OH (silanol groups), which affects the available volume of the pores of EMM-23 and reduces the structural stability.
[0010] US5489424 discloses an extra-large pore silicate molecular sieve UTD-1 and its preparation method, in which the organic structure directing agent is a complex metal complex (bis(pentamethylcyclopentadienyl)cobalt cation). US6043179 discloses an extra-large pore silicate molecular sieve CIT-5 and its preparation method, in which the organic structure directing agent is a complex drug derivative (methylsparteinium cation). These two materials are not widely used in industry due to two shortcomings: (1) these two zeolite structures only contain one-dimensional 14-membered ring channels, which do not meet the requirements of multi-dimensional channels needed for industrial catalytic reactions; (2) the organic templates used in the synthesis of these two materials are very expensive, thus increasing the cost of commercialization.
[0011] CN104370296A discloses a large-pore silicate molecular sieve NUD-1 and its synthesis method. The zeolite structure shows that double four-membered rings, three-membered rings and double three-membered rings are alternately connected to form a channel structure with alternating ten-membered rings and twelve-membered rings, and these two types of channels are each intersected by an 18-membered ring channel. However, the molecular sieve is a germanium-containing molecular sieve.
[0012] Therefore, a need exists for germanium-free, low-cost, and stable silicate molecular sieve materials with multidimensional oversized pores.
[0013] Meanwhile, titanosilica molecular sieves are a new kind of molecular sieves containing heteroatoms that have been developed since the early 1980s. At present, the known titanosilicate zeolites are TS-1 with MFI structure, TS-2 with MEL structure, beta zeolite Ti-beta, and mesoporous materials Ti-MCM-41 and Ti-MCM-48, etc. This kind of molecular sieve has excellent catalytic activity and specific oxidation ability in many organic oxidation reactions, such as olefin epoxidation, hydroxylation of aromatic compounds, oximation of cyclohexanone, oxidation of alcohols, etc. They have important application value in industry as redox molecular sieve catalysts. Take TS-1 as an example, its preparation method was first disclosed in 1981 by Marco Taramasso et al., from Italy (see GB2071071A, USP4410501). It not only has a good catalytic oxidation effect on organic compounds due to titanium atoms in this zeolite, but also has the shape-selective effect of ZSM-5 molecular sieve with high stability. In the oxidation reaction of organics involving TS-1, low concentration of hydrogen peroxide can be used as an oxidant with good selectivity, which can avoid problems such as industrial complexity and environmental pollution in the traditional oxidation process compared with traditional oxidation systems, and realize the unparalleled advantages of energy saving and environmental protection. According to a study by Li Can et al. from Dalian Institute of Chemical Physics in China, the direct evidence of framework Ti atoms is the absorption peak at about 220 nm in the UV-Vis absorption spectrum, which indicates a tetracoordinated Ti atom in the zeolite framework (see Angew. Chem. Int. Ed., 1999, 38, 2220-2222), and the tetracoordinated Ti atom is the active center in the catalytic reaction.
[0014] The pore size of TS-1 and TS-2 is about 5.5 angstroms, and that of Ti-Beta is 6.5 angstroms. To have good shape selectivity, the size of the reactant molecules should be smaller than the zeolite pore size, which severely limits the further applications of the mentioned zeolite materials. Meanwhile, generally, Ti-MCM-41 and Ti-MCM-48 only have adjustable mesopores with sizes between 15 and 100 angstroms. Therefore, there is no titanosilicate zeolite material that contains 7-15 angstrom micropores, which is necessary, as this pore size is just in the molecular size range of many high-value chemicals. [Prior art documents] [Patent documents]
[0015] [Patent Document 1] U.S. Patent No. 2,882,243 [Patent Document 2] U.S. Patent No. 3,130,007 [Patent Document 3] U.S. Pat. No. 3,709,979 [Patent Document 4] U.S. Pat. No. 3,832,449 [Patent Document 5] U.S. Pat. No. 4,410,501 [Patent Document 6] U.S. Pat. No. 3,702,886 [Patent Document 7] U.S. Patent No. 2,882,244 [Patent Document 8] International Publication No. 2013 / 019462A1 [Patent Document 9] U.S. Pat. No. 5,489,424 [Patent Document 10] U.S. Patent No. 6,043,179 [Patent Document 11] China Patent Application Publication No. 104370296A [Patent Document 12] UK Patent Application Publication No. 2071071A [Patent Document 13] U.S. Patent No. P4410501 [Non-patent literature]
[0016] [Non-Patent Document 1] https: / / europe.iza-structure.org / IZA-SC / DatabaseHelp_Structures.html#CS [Non-Patent Document 2] J. Sun et al., Nature, 2009, 458, 1154-1157 [Non-Patent Document 3] J. Jiang et al., Science, 2011, 333, 1131-1134 [Non-Patent Document 4] A. Corma et al., Nature 2006, 443, 842-845 [Non-Patent Document 5] F.-J. Chen et al., Angew. Chem. Int. Ed. 2014, 53,9592-9596 [Non-Patent Document 6] KG Strohmaier et al., J. Am. Chem. Soc. 2003, 125, 16035-16039 [Non-Patent Document 7] Angew. Chem. Int. Ed., 1999, 38, 2220-2222 [Non-Patent Document 8] https: / / topospro.com / software / Summary of the Invention [Problem to be solved by the invention]
[0017] In the first aspect, the present invention provides a completely new extra-large pore silicate molecular sieve ZEO-1, which is a germanium-free, high-silica or pure-silica extra-large pore molecular sieve material, which not only has very important practical value, but also has very important theoretical significance for enriching the molecular sieve structure family. The ultra-macroporous silicate molecular sieve of the present invention not only adds a new member to the family of ultra-macroporous molecular sieve materials, but also provides a new option for the use of such molecular sieve materials in industrial catalysis. Furthermore, titanium atoms are successfully introduced into the framework of the zeolite ZEO-1 of the present invention, which fills the deficiency in the field of titanosilicate extra-large pore zeolites, provides a new option for the use of molecular sieve materials in industrial catalysis, and has important practical value. [Means for solving the problem]
[0018] The ZEO-1 molecular sieve of the present invention is (TiO2) y ·(HAO2) x It has a chemical composition of SiO2, where A is a boron group element, preferably Al or B; 0≦x≦1.0, preferably 0≦x≦0.5, more preferably 0≦x<0.2, most preferably 0.01≦x≦0.1; 0≦y<0.2, preferably 0.01≦y≦0.1.
[0019] The molecular sieve framework has the topological characteristics shown in Table 1 below.
[0020] [Table 1]
[0021] T1 to T21 represent the 21 topologically distinct T atoms of the structure of the extra-large pore zeolite ZEO-1 of the present invention, and N1 to N12 represent the coordination sequences of these T atoms in the first to twelfth shells. Due to different orders of naming of the T atoms, the 21 topologically independent T atoms named in different orders may not correspond one-to-one to the coordination sequences and vertex symbols of the T atoms in the order in this table, but the structure belonging to the ZEO-1 topology includes all and only the coordination sequences and vertex symbols of the 21 topologically independent T atoms in this table, and the coordination sequences and vertex symbols correspond one-to-one.
[0022] The crystallographic structure of molecular sieves has a three-dimensional intersecting channel system of (16+12) x (16+12) x (16+12) membered rings.
[0023] The molecular sieves have the X-ray powder diffraction characteristics shown in Table 2 below.
[0024] [Table 2]
[0025] In the above data, w, mw, m, s, and vs represent the relative intensities of the diffraction peaks, where w is weak, mw is slightly weak, m is moderate, s is strong, and vs is very strong, which are known to those skilled in the art. Generally speaking, w is less than 10, mw is 10-20, m is 20-40, and s is 4. 0 ~70 and vs >70.
[0026] In a second aspect, the present invention provides a method for preparing a ZEO-1 molecular sieve, comprising the steps of: (1) mixing a silicon source, a boron group element compound, an organic template, water, a mineralizer, and optionally a titanium source to obtain a synthesis mixture; (2) crystallizing the mixture; (3) calcining the crystallized product to remove the template. Including, The organic template has the following general formula: [ka] (Wherein, R1 is cyclohexyl; R2 and R3 are phenyl or cyclohexyl; R4 is C 1~8 Alkyl, preferably C 1~4 Alkyl, more preferably C 1~2 alkyl; and X is phosphorus or nitrogen, preferably phosphorus. having a tetrahedral spatial arrangement represented by A method is further provided.
[0027] In a third aspect, the present invention further provides a molecular sieve composition comprising the ZEO-1 molecular sieve of the present invention and a binding agent (binder).
[0028] In a fourth aspect, the molecular sieve composition of the present invention can be used as an adsorbent or a catalyst. [Brief description of the drawings]
[0029] [Figure 1] 1 shows X-ray powder diffraction patterns (wavelength: CuKα) of the ZEO-1 molecular sieve without titanium incorporation according to the present invention before and after calcination at temperatures of 600° C. and 1000° C. to remove the template. [Diagram 2] 1 is an X-ray diffraction pattern (synchrotron radiation at a wavelength of 0.457926 Angstroms) of the as-synthesized ZEO-1 molecular sieve without titanium incorporation in the present invention. [Diagram 3] 1 is a scanning electron micrograph (SEM) of ZEO-1 molecular sieve without titanium incorporation in accordance with the present invention. [Figure 4] FIG. 2 is a diagram of the channel structure of the ZEO-1 molecular sieve of the present invention. [Diagram 5]1 shows X-ray diffraction patterns (wavelength: CuKα) of titanosilicate ZEO-1 molecular sieves of the present invention (in-situ synthesized sample and calcined sample). [Figure 6] 1 is a scanning electron micrograph (SEM) of the titanosilicate ZEO-1 molecular sieve of the present invention. [Figure 7] 1 is an ultraviolet spectrogram of titanosilicate ZEO-1 molecular sieve of the present invention (in-situ synthesized sample and calcined sample). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] The crystal structure of the ZEO-1 molecular sieve of the present invention is shown in Figure 4. From Figure 4, it can be seen that there are 16- and 12-ring channels penetrating in both the a-axis and b-axis directions of the ZEO-1 crystal structure. In addition, there are 16- and 12-ring channels in the direction close to the (a+b+c) axis of the ZEO-1 crystal structure. Thus, the structure can be described as a three-dimensional intersecting channel system of (16+12) x (16+12) x (16+12) rings.
[0031] The ZEO-1 molecular sieve of the present invention is subjected to structural and topological analysis. The molecular sieve framework structure has 21 topologically independent T atoms, 43 topologically distinct edges (lines formed by adjacent T atoms and T atoms), 41 topologically distinct faces (faces formed by T atoms), and 19 topologically distinct tiles formed by T atoms. Among them, the topological characteristics (including the coordination sequence and vertex symbols) of the 21 topologically independent T atoms of the framework structure of the ZEO-1 material are shown in Table 1.
[0032] Among the 19 different tiles in the framework structure of ZEO-1 molecular sieve, there are three kinds of supercage structures: the first one constructed by four 16-membered rings, the second one by two 16-membered rings and two 12-membered rings, and the third one containing four 12-membered rings. Compared with the supercage in zeolite Y (structure code: FAU) with four 12-membered rings (this supercage is also the important catalytic center of zeolite Y), ZEO-1 has a larger pore size, a larger available volume, and a richer channel diversity.
[0033] After calcination, the ZEO-1 molecular sieve of the present invention has the following properties: (TiO2) y ·(HAO2) x It has the chemical composition SiO2 (wherein A is a boron group element, preferably Al or B, 0≦x≦1.0, preferably 0≦x≦0.5, more preferably 0≦x<0.2, most preferably 0.01≦x≦0.1, and 0≦y<0.2, preferably 0.01≦y≦0.1).
[0034] After calcined in air at 1000°C for 3 hours to remove template molecules, the ZEO-1 molecular sieve of the present invention still maintains a stable framework (as shown in Figure 2), showing better stability compared with other reported extra-large pore molecular sieve materials. Meanwhile, heteroatoms, such as aluminum, boron, etc., may be directly introduced into the molecular sieve framework. These features give the molecular sieve materials a prospect of potential applications in the fields of adsorption, separation, catalysis, etc.
[0035] The X-ray diffraction pattern of the titanium-containing ZEO-1 molecular sieve of the present invention is shown in Figure 5. In comparison with the X-ray diffraction pattern of the ZEO-1 molecular sieve of Figure 1, similar positions and intensities of the diffraction peaks are observed, indicating that the obtained titanosilicate material has the structure of ZEO-1 zeolite.
[0036] The SEM images of the titanium-containing ZEO-1 molecular sieve of the present invention are shown in Figure 6, which indicates that the as-synthesized titanium-containing ZEO-1 molecular sieve has uniform particle size and good crystallinity, without impurities such as amorphous compounds or anatase. Its UV-Vis spectrum is shown in Figure 7. Both the titanium-containing ZEO-1 molecular sieve before and after calcination have a strong absorption peak at about 220 nm, which corresponds to Ti atoms in a four-coordinated state in the molecular sieve framework, proving that Ti atoms have been successfully introduced into the ZEO-1 molecular sieve framework.
[0037] In the method for preparing the ZEO-1 molecular sieve of the present invention, specific examples of organic templates include, but are not limited to, any one or more of those shown in Table 3 below.
[0038] [Table 3]
[0039] The organic template is preferably any one or more selected from the group consisting of template 1, template 6, template 7, and template 8, more preferably any one or more selected from the group consisting of template 6 and template 8.
[0040] The method for the synthesis of the ZEO-1 molecular sieve of the present invention more specifically comprises the following steps: (1) Under static or dynamic stirring, a silicon source, a boron group element compound, an organic template, water, a mineralizer, and optionally a titanium source are mixed uniformly and in a ratio to form a mixture having a chemical composition of rROH:aHF:yTiO2:xA2O3:SiO2:wH2O, where R represents the organic template cation; A is a boron group element, preferably Al or B; r, a, x, and y are the same; and corresponding value intervals of w are: r=0.1-5.0, a=0-5.0, x=0-1.0, y=0-0.2, w=1-100, preferably r=0.1-5.0, a=0-5.0, x=0-0.1, y=0-0.2, w=1-100, more preferably r=0.1-2.0, a=0-2.0, x=0.005-0.05, y=0.01-0.1, w=5-30); (2) For crystallization, the reaction gel was placed under an infrared lamp or in an oven to remove excess solvent, and then the gel was transferred to a stainless steel autoclave at a temperature of 80-240°C, preferably 120-220°C, for 1-60 days, preferably 2-45 days under sealed conditions; (3) After crystallization, washing, centrifugation, and drying, the as-synthesized products were obtained. The as-synthesized samples were then calcined at 400–650 °C in air for 2–5 h to remove the template.
[0041] The silicon source may be at least one selected from the group consisting of silicic acid, silica gel, silica sol, tetraalkyl orthosilicate, and water glass, preferably water glass, silica sol, or tetraethyl orthosilicate. The boron group element compound may be at least one selected from the group consisting of sodium metaaluminate, aluminum isopropoxide, aluminum sulfate hexahydrate, aluminum hydroxide, and boric acid, preferably sodium metaaluminate, aluminum isopropoxide, aluminum sulfate hexahydrate, or boric acid. The titanium source may be one or a mixture of two or more of tetrabutyl orthotitanate, titanium tetrachloride, titanium trichloride, and titanium sulfate. The mineralizer is OH from an alkaline solution of an organic template. -or F from further added HF or NH4F - The addition of a mineralizer can accelerate the crystallization of the molecular sieve and can be beneficial for the orientation of the structure. The preparation method of the present invention can be carried out under neutral conditions (using F as a mineralizer). - (HF-free, OH as mineralizer) and alkaline conditions (HF-free, OH as mineralizer) - ) can be used to obtain the ZEO-1 molecular sieve of the present invention.
[0042] In the preparation method of the present invention, no germanium or germanium-containing compounds are used.
[0043] The various materials can be added and mixed in any order. For example, a boron group element (such as Al or B) may be first added to the obtained alkaline solution of the template, stirred and dissolved, and then a suitable silicon source and titanium source can be added. If necessary, a mineralizer is added after uniform stirring, and the material is heated under an infrared lamp or in an oven to remove excess solvent in the system and obtain the target gel.
[0044] Prior to preparation of the reaction gel, all of the organic cationic templates may be exchanged into hydroxide form by ion exchange resin and their concentration quantified by 0.1 M hydrochloric acid solution for later use, or they may be directly introduced in the form of chloride, bromide, or iodide salts.
[0045] In step (2), the oven temperature may be, for example, 80°C.
[0046] The crystallization conditions may include, for example, a crystallization temperature of 80°C to 240°C, preferably 120°C to 220°C, and more preferably 140°C to 210°C; and a crystallization time of 1 to 60 days, preferably 2 to 45 days, and more preferably 3 to 30 days.
[0047] The mixture in the preparation method of the present invention may further contain seed crystals. The content of the seed crystals may be 0.01 mass ppm to 10000 mass ppm. The ZEO-1 molecular sieve of the present invention can be used as the seed crystals. The presence of the seed crystals can accelerate the reaction process and reduce the reaction cost.
[0048] In step (3), washing, centrifugation, and drying can be performed in any manner conventionally known in the art. For example, washing can be performed multiple times with water or ethanol; and drying can be performed by oven drying. EXAMPLES
[0049] In order to more clearly illustrate the present invention, the following examples are provided, which in no way limit the scope of protection of the present invention.
[0050] Example 1: Synthesis of templates To illustrate the general process for the synthesis of templates, template 6 was taken as an example. 28.04g tricyclohexylphosphine and 150ml acetonitrile were mixed in a 250ml round bottom flask. At room temperature, 21.29g methyl iodide was added dropwise to the mixture. The system was kept at room temperature under stirring for 2 days, and the solvent was removed from the mixture by rotary evaporation to obtain the crude product, which was recrystallized from ethanol to obtain 40.55g product with a yield of 96%. The product was characterized by liquid NMR (D2O) and electrospray mass spectrometry to confirm it was the target compound.
[0051] The resulting product was dispersed in 400 mL of deionized water, and pretreated 717 strong base anion exchange resin (manufacturer: Sinopharm Group Co., Ltd., China) was used for anion exchange in a column to obtain an aqueous solution of template agent 6. A suitable amount of this solution was weighed and titrated with 0.1 mol / L hydrochloric acid solution using phenolphthalein as indicator. The titrated structure confirmed the exchange ratio of iodide salt to hydroxide group up to 97%.
[0052] Example 2: Preparation of ZEO-1 molecular sieves (Example 2-1) According to the molar ratio of 0.5 ROH:0.5 HF:0.01 Al2O3:SiO2:5 H2O, the gel for the synthesis of molecular sieves was prepared by the following steps: a suitable amount of template solution in Example 1 after exchange was weighed out, 0.04 mmol (0.008 g) of aluminum isopropoxide powder was added thereto, and stirred for about half an hour, then 2 mmol (0.417 g) of tetraethyl orthosilicate was added, and stirred at room temperature for about 2 hours, so that tetraethyl orthosilicate was completely dissolved, and then a corresponding amount of hydrofluoric acid solution was added according to the above ratio, stirred uniformly, and the mixed gel was placed under an infrared lamp or in an oven at 80°C to remove excess solvent to the theoretical mass. Finally, the obtained mixture gel was transferred to a 5 mL stainless steel autoclave with a Teflon liner, and crystallized under sealed conditions at 175°C for 28 days, and the product was washed twice with water and twice with ethanol, and oven-dried for use. The product was directly subjected to phase identification by X-ray powder diffraction and the pattern was confirmed as that of ZEO-1. A suitable amount of the sample was calcined in a muffle furnace at 600°C in air for 2 hours to remove the template, and the product was washed with water, centrifuged and dried. Elemental analysis showed that the Si / Al ratio was 20.5 and its molecular formula was (HAIO2). 0.047 ·SiO2.
[0053] (Example 2-2) According to the molar ratio of 0.5 ROH:0.5 HF:0.02 Al2O3:SiO2:7 H2O, the gel for the synthesis of molecular sieves was prepared by the following steps: a suitable amount of template solution in Example 1 after exchange was weighed out, 0.08 mmol (0.016 g) of aluminum isopropoxide powder was added thereto, and stirred for about half an hour, then 2 mmol (0.417 g) of tetraethyl orthosilicate was added, and stirred at room temperature for about 2 hours, so that tetraethyl orthosilicate was completely dissolved, and then a corresponding amount of hydrofluoric acid solution was added according to the above ratio, stirred uniformly, and the mixed gel was placed under an infrared lamp or in an oven at 80°C to remove excess solvent to the theoretical mass. Finally, the obtained mixture gel was transferred to a 5 mL stainless steel autoclave with a Teflon liner, and crystallized under sealed conditions at 190°C for 7 days, and the product was washed with water twice, ethanol twice, and oven-dried for use. The product was directly subjected to phase identification by X-ray powder diffraction and the pattern was confirmed as that of ZEO-1. A suitable amount of the sample was calcined in a muffle furnace at 600°C in air for 2 hours to remove the template, and the product was washed with water, centrifuged and dried. Elemental analysis showed that the Si / Al ratio was 14.6 and its molecular formula was (HAIO2). 0.064 ·SiO2.
[0054] (Example 2-3) According to the molar ratio of ROH:Al2O3:SiO2:HO of 0.5:0.01, the gel for the synthesis of molecular sieve was prepared by the following steps: a suitable amount of template solution in Example 1 after exchange was weighed, 0.04 mmol (0.008 g) of aluminum isopropoxide powder was added thereto, stirred for about half an hour, then 2 mmol (0.417 g) of tetraethyl orthosilicate was added thereto, stirred at room temperature for about 2 hours, so that tetraethyl orthosilicate was completely dissolved, and the mixed gel was placed under infrared lamp or in an oven at 80°C to remove excess solvent to theoretical mass. Finally, the obtained mixture gel was transferred to a 15 mL stainless steel autoclave with a Teflon liner and crystallized under sealed conditions at 175°C for 30 days, and the product was washed with water twice and ethanol twice, and oven-dried for use. The product was directly subjected to phase identification by X-ray powder diffraction, and the pattern was confirmed as that of ZEO-1. A suitable amount of the sample was calcined in a muffle furnace at 600°C in air for 2 hours to remove the template, and the product was washed with water, centrifuged, and dried. Elemental analysis showed that the Si / Al ratio was 20.8 and the molecular formula was (HAIO2). 0.046 ·SiO2.
[0055] (Examples 2-4) According to the molar ratio of ROH of 0.5:Al2O3 of 0.0167:SiO2 of 10:H2O of 10, the gel for the synthesis of molecular sieve was prepared by the following steps: a suitable amount of template solution in Example 1 after exchange was weighed out, 0.067 mmol (0.013 g) of aluminum isopropoxide powder was added thereto, and stirred for about half an hour, then 2 mmol (0.417 g) of tetraethyl orthosilicate was added thereto, and stirred at room temperature for about 2 hours, so that tetraethyl orthosilicate was completely dissolved, and the mixed gel was placed under infrared lamp or in an oven at 80°C to remove excess solvent to theoretical mass. Finally, the obtained mixture gel was transferred to a 15 mL stainless steel autoclave with a Teflon liner and crystallized under sealed conditions at 190°C for 15 days, and the product was washed with water twice and ethanol twice, and oven-dried for use. The product was directly subjected to phase identification by X-ray powder diffraction, and the pattern was confirmed as that of ZEO-1. A suitable amount of the sample was calcined in a muffle furnace at 600°C in air for 2 hours to remove the template, and the product was washed with water, centrifuged, and dried. Elemental analysis revealed a Si / Al ratio of 14.5 and a molecular formula of (HAIO2). 0.065 ·SiO2.
[0056] All of the molecular sieve materials in Examples 2-1 to 2-4 obtained molecular sieve materials with intact structures after calcination (at 600°C or 1000°C), indicating that the structures were stable. The X-ray powder diffraction patterns of the as-synthesized powder samples of the molecular sieves and the molecular sieves after high-temperature calcination are shown in Figures 1 and 2. The crystals of the ZEO-1 sample with suitable size were selected, and the scanning electron micrographs are shown in Figure 3.
[0057] (Examples 2-5) The molecular sieves of Examples 2-1 to 2-4 were subjected to continuous rotation electron diffraction (cRED) testing, and the structural analysis results showed that the ZEO-1 molecular sieve structure had tetragonal symmetry in the I41 / amd space group, and the unit cell parameters ( FIG. 2 ) obtained after refinement of synchrotron radiation diffraction at a wavelength of 0.457926 Å were a=b=43.50217(10)Å, c=24.94918(9)Å, V=47214.8(3)Å. 3 It was shown that.
[0058] Topological analysis was carried out using the crystal information file (CIF file) obtained after the cRED test. The topological analysis software was based on ToposPro 5.3.0.2, and the analysis process and method were based on the operation manual provided on the official website of the software (see ToposPro official website: https: / / topospro.com / software / ).
[0059] The analysis results showed that the framework structure of the molecular sieve had 21 topologically independent T atoms, 43 topologically distinct edges, 41 topologically distinct faces, and 19 topologically distinct tiles composed of T atoms. More specific topological characteristics of the framework structure of the ZEO-1 molecular sieve are shown in Table 2.
[0060] Example 3: Preparation of titanium-containing ZEO-1 molecular sieve (Example 3-1) According to the molar ratio of SiO2:0.02 Al2O3:0.04 TiO2:0.5 ROH:20 H2O, the gel for the synthesis of molecular sieve was prepared by the following steps: weigh out a suitable amount of base solution of template 6 after exchange, add 0.08 mmol (0.016 g) of aluminum isopropoxide powder thereto, stir for about half an hour, then add 2 mmol (0.417 g) of tetraethyl orthosilicate, and stir at room temperature for about 2 hours, so that tetraethyl orthosilicate is completely dissolved, finally add 0.08 mmol (0.027 g) of tetrabutyl orthotitanate, stir overnight, and place the mixed gel under infrared lamp or in an oven at 80 °C to remove excess solvent to theoretical mass. Finally, the mixture gel was transferred to a 15 mL stainless steel autoclave with a Teflon liner and crystallized under sealed conditions at 190°C for 30 days, and the product was washed twice with water and twice with ethanol and dried in an oven for use. The product was directly subjected to phase identification by X-ray powder diffraction, and the pattern was confirmed as that of ZEO-1. A suitable amount of the sample was calcined in a muffle furnace at 600°C in air for 2 hours to remove the template, and the sample was washed with water and dried. Elemental analysis revealed that its molecular formula was H 0.04 Al 0.04 Ti 0.04 S 0.92 It was shown to be O2.
[0061] (Example 3-2) According to the molar ratio of SiO2:0.01 Al2O3:0.02 TiO2:0.5 ROH:15 H2O, the gel for the synthesis of molecular sieve was prepared by the following steps: weigh out a suitable amount of base solution of template 6 after exchange, add 0.04 mmol (0.008 g) of aluminum isopropoxide powder thereto, stir for about half an hour, then add 2 mmol (0.417 g) of tetraethyl orthosilicate, and stir at room temperature for about 2 hours, so that tetraethyl orthosilicate is completely dissolved, finally add 0.04 mmol (0.014 g) of tetrabutyl orthotitanate, stir overnight, and place the mixed gel under infrared lamp or in an oven at 80 °C to remove excess solvent to theoretical mass. Finally, the mixture gel was transferred to a 15 mL stainless steel autoclave with a Teflon liner and crystallized under sealed conditions at 175°C for 30 days, and the product was washed twice with water and twice with ethanol and dried in an oven for use. The product was directly subjected to phase identification by X-ray powder diffraction, and the pattern was confirmed as that of ZEO-1. A suitable amount of sample was calcined in a muffle furnace at 600°C in air for 2 hours to remove the template, and the sample was washed with water and dried. Elemental analysis revealed that its molecular formula is H 0.02 Al 0.02 Ti 0.02 S 0.96 It was shown to be O2.
[0062] (Example 3-3) According to the molar ratio of SiO2:0.02 Al2O3:0.02 TiO2:0.5 ROH:0.5 HF:7 H2O, the gel for the synthesis of molecular sieve was prepared by the following steps: weigh out a suitable amount of base solution of template 6 after exchange, add 0.08 mmol (0.016 g) of aluminum isopropoxide powder thereto, stir for about half an hour, then add 2 mmol (0.417 g) of tetraethyl orthosilicate, stir at room temperature for about 2 hours, so that tetraethyl orthosilicate is completely dissolved, then add 0.04 mmol (0.014 g) of tetrabutyl orthotitanate, stir overnight, finally add the corresponding amount of hydrofluoric acid solution according to the above ratio, stir evenly, and place the mixed gel under infrared lamp or in oven at 80 °C to remove excess solvent to theoretical mass. Finally, the mixture gel obtained was transferred to a 15 mL stainless steel autoclave with a Teflon liner and reacted under sealed conditions at 175°C for 30 days, the product was washed twice with water and twice with ethanol, and oven-dried for use. The product was directly subjected to phase identification by X-ray powder diffraction, and the pattern was confirmed as that of ZEO-1. A suitable amount of sample was calcined in a muffle furnace at 600°C in air for 2 hours to remove the template, and the sample was washed with water and dried. Elemental analysis revealed that its molecular formula was H 0.04 Al 0.04 Ti 0.02 S 0.94 It was shown to be O2.
[0063] (Examples 3-4) According to the molar ratio of SiO2:0.02, B2O3:0.04, TiO2:0.5, ROH:10, H2O, the gel for the synthesis of molecular sieve was prepared by the following steps: weigh out a suitable amount of base solution of template 6 after exchange, add 0.08 mmol (0.005 g) of boric acid thereto, stir for about half an hour, then add 2 mmol (0.417 g) of tetraethyl orthosilicate, stir at room temperature for about 2 hours, so that tetraethyl orthosilicate is completely dissolved, finally add 0.08 mmol (0.027 g) of tetrabutyl orthotitanate, stir overnight, and place the mixed gel under infrared lamp or in oven at 80°C to remove excess solvent to theoretical mass. Finally, the mixture gel obtained was transferred to a 15 mL stainless steel autoclave with a Teflon liner and reacted under sealed conditions at 190°C for 30 days, and the product was washed twice with water and twice with ethanol and dried in an oven for use. The product was directly subjected to phase identification by X-ray powder diffraction, and the pattern was compared and confirmed as that of ZEO-1. A suitable amount of sample was calcined in a muffle furnace at 600°C in air for 2 hours to remove the template, and the sample was washed with water and dried. Elemental analysis revealed that its molecular formula is H 0.04 B 0.04 Ti 0.04 S 0.92 It was shown to be O2.
[0064] (Examples 3-5) According to the molar ratio of SiO2:0.02 B2O3:0.02 TiO2:0.5 ROH:15 H2O, the gel for the synthesis of molecular sieve was prepared by the following steps: weigh out a suitable amount of base solution of template 6 after exchange, add 0.08 mmol (0.005 g) of boric acid thereto, stir for about half an hour, then add 2 mmol (0.417 g) of tetraethyl orthosilicate, stir at room temperature for about 2 hours, so that tetraethyl orthosilicate is completely dissolved, finally add 0.04 mmol (0.014 g) of tetrabutyl orthotitanate, stir overnight, and place the mixed gel under infrared lamp or in oven at 80°C to remove excess solvent to theoretical mass. Finally, the mixture gel was transferred to a 15 mL stainless steel autoclave with a Teflon liner and crystallized under sealed conditions at 175°C for 30 days, and the product was washed twice with water and twice with ethanol and oven-dried for use. The product was directly subjected to phase identification by X-ray powder diffraction and confirmed to be that of ZEO-1 by comparison. A suitable amount of sample was calcined in a muffle furnace at 600°C in air for 2 hours to remove the template, and the sample was washed with water and dried. Elemental analysis showed that its molecular formula was H 0.04 B 0.04 Ti 0.02 S 0.94 It was shown to be O2.
Claims
1. (TiO 2 ) y ・(HAO 2 ) x SiO 2 wherein A is a boron group element; 0≦x≦1.0; and 0≦y<0.2, A silicate molecular sieve, characterized in that the crystal structure of the molecular sieve has a three-dimensional intersecting channel system of (16+12) x (16+12) x (16+12) membered rings and has the X-ray powder diffraction characteristics shown in Table 2 below. 【Table 1】
2. 2. The silicate molecular sieve of claim 1, wherein the framework of the molecular sieve has the topological characteristics shown in Table 1 below. 【Table 2】 3. The silicate molecular sieve according to claim 1, wherein A is Al or B in (TiO 2 ) y ·(HAO 2 ) x ·SiO 2 .
4. The silicate molecular sieve according to claim 1, wherein in (TiO 2 ) y ·(HAO 2 ) x ·SiO 2 , 0.01≦x≦0.1 and 0.01≦y≦0.
1.
5. A method for synthesizing the silicate molecular sieve according to any one of claims 1 to 4, comprising the steps of: (1) mixing a silicon source, a boron group element compound, an organic template, water, a mineralizer, and optionally a titanium source to obtain a mixture; (2) crystallizing the mixture; (3) Calcining the crystallized product to remove the template. Including, The organic template has the following general formula: 【Chemistry 1】 (In the formula, R 1 is cyclohexyl; R 2 and R 3 is phenyl or cyclohexyl; R 4 C 1~8 alkyl; and X is phosphorus or nitrogen. The method of claim 1, having a tetrahedral spatial arrangement represented by:
6. The organic template is 【Chemistry 2】 Any one or more selected from The method according to claim 5, characterized in that
7. (1) Under stirring, a silicon source, a boron group element compound, an organic template, water, a mineralizer, and optionally a titanium source are mixed uniformly in the ratio rROH:aHF:yTiO 2 :xA 2 O 3 : SiO 2 :wH 2 forming a reaction gel with the resulting mixture having a chemical composition of O, where R represents a positively charged group of the organic template; A is a boron group element; and the corresponding ranges of values of r, a, x, and w are r=0.1-5.0, a=0-5.0, x=0-1.0, y=0-0.2, and w=1-100; (2) placing the reaction gel under an infrared lamp or in an oven for crystallization, and after removing excess solvent, transferring the reaction gel into a stainless steel autoclave to react under sealed condition at a temperature of 80-240°C for 1-60 days; (3) Washing and drying the crystallized product, then calcining it at 400-650° C. in air for 2-5 hours to remove the template.
7. The method according to claim 5 or 6, characterized in that it comprises:
8. The method according to any one of claims 5 to 7, characterized in that the silicon source is at least one selected from the group consisting of silicic acid, silica gel, silica sol, tetraalkyl orthosilicate, and water glass.
9. The method according to any one of claims 5 to 8, characterized in that the boron group element compound is at least one selected from the group consisting of sodium metaaluminate, aluminum isopropoxide, aluminum sulfate hexahydrate, aluminum hydroxide, and boric acid.
10. The method according to any one of claims 5 to 9, characterized in that the titanium source is one or a mixture of two or more of tetrabutyl orthotitanate, titanium tetrachloride, titanium trichloride and titanium sulfate.
11. The mineralizer is OH from the alkaline aqueous solution of the organic template. - or further added HF or NH 4 F from F - The method according to any one of claims 5 to 10, characterized in that
12. The method according to any one of claims 5 to 11, characterized in that the crystallization conditions in step (2) comprise a crystallization temperature of 80 to 240°C and a crystallization time of 1 to 60 days.
13. The method according to any one of claims 5 to 12, characterized in that the mixture further comprises 0.01 ppm to 10000 ppm by weight of seed crystals.
14. The method of claim 13, wherein the seed crystals comprise a molecular sieve according to any one of claims 1 to 4.
15. A molecular sieve composition comprising the molecular sieve of any one of claims 1 to 4 and a binder.
16. 16. Use of the molecular sieve composition of claim 15 as an adsorbent or catalyst.
Citation Information
Patent Citations
Large blocked TS-1 molecular sieve with high catalytic activity and synthetic method thereof
CN101696019A
Super-macroporous silicate molecular sieve NUD-1 and preparation method thereof
CN104370296A
Aluminosilicate molecular sieve SCM-6, and synthetic method and use thereof
CN105217651A
Titanuim silica
GB2071071A
Titanium-containing mordenite and its production
JP1997077511A